الفهرسة الوصفية في مكتبة المعهد التقني /الموصل مع الاشارة الى الفهرسة الالية للمكتبة - بديعة يوسف عبدالرحمن خدان; أمثال شهاب احمد الحجار (PROSPECTIVE RESEARCHES, 2023)
This Research (Descriptive cataloging in the library of Technical institute\ Mosul) has focused on the importance of evaluating "Card Catalog" of the library of Mosul Technical Institute. This was done through determining the type, size, and differences the cataloging suffers from and showing its effect on recalling the information resources easily and quickly. This research has followed the case study method for manual descriptive cataloging in the library of Mosul Technical Institute and for all information resources. The extent to which the rules of applying the Anglo-American cataloging on the information resources was known. This was done through repealing the descriptive cataloging of (50) books the library received since 1990. These cards were compared to the cards made by librarians in the library. A field study for computerized catalog of the library was achieved, beside a field study for the catalogue card of the library. The users' opinion of the performance of the library manual and computerized catalog cards was reviewed to know the extent of using them. This researched has shown that these were mistakes and differences in all field of the description. No card was free from the mistakes and differences. No cards having all the elements. The research has come with a number of recommendations, all aiming at re-building the cards. This could be done throng the ideas of specialists in the field of information and libraries. Continuous renewing of the rules and tools used in descriptive cataloging, and following the improvements and modifications is necessary to improve the situation of the catalog.